2010
DOI: 10.1111/j.1479-828x.2009.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and second trimester pregnancy termination for fetal abnormality in Western Australia: Worth the effort

Abstract: The introduction of mifepristone priming prior to second trimester medical termination with misoprostol has resulted in a significant reduction in the duration of the termination procedure and length of inpatient stay. These observed benefits of mifepristone provide objective support for the decision to permit use of this medication in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
3
16
3
Order By: Relevance
“…4 We planned that 300 women would be recruited to the study (100 per group). It was expected from our previous observations that at least 62% of women recruited into the standard treatment arm would deliver in less than 12 hours and 88% within 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 We planned that 300 women would be recruited to the study (100 per group). It was expected from our previous observations that at least 62% of women recruited into the standard treatment arm would deliver in less than 12 hours and 88% within 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] However, there are recognized complications with medical abortion. The median gestation at recruitment was oral 19.…”
mentioning
confidence: 99%
“…In 2010, Dickinson et al reported the results of a prospective WA study of second-trimester terminations of pregnancy for severe fetal abnormality, in which 189 women were treated with misoprostol alone (prior to the granting of AP approval for mifepristone use to doctors in the hospital concerned) and 199 with mifepristone priming followed by misoprostol (once approval was granted) [32]. The median abortion duration was 15.5 h in the misoprostol group and 8.6 h in the mifepristone/misoprostol group.…”
Section: Experience Of Medical Abortion In Wamentioning
confidence: 98%
“…The addition of mifepristone for priming (200 mg 24–48 hours prior, n = 199) to misoprostol alone (400 mcg every 6 hours, maximum 48 hours, n = 189) in a sequential cohort for termination at 14–24 weeks (median 19 weeks) was found to reduce the median abortion duration from 15.5 to 8.6 hours and the duration of hospitalisation from 31.5 to 27.2 hours [17]. Increasing gestation was associated with a longer duration of termination regardless of the regime used (6.5 hours for 14–18 weeks and 10.5 hours for 20–28 weeks in the mifepristone priming group).…”
Section: Resultsmentioning
confidence: 99%
“…It appears that the methods used for termination of pregnancy in the first and second trimesters are also transferrable [14, 15, 17, 2527]. …”
Section: Discussionmentioning
confidence: 99%